Pharmacogenetic Association Study of Warfarin Safety Endpoints in Puerto Ricans - Valentín, Isa I.; Rivera, Giselle; Nieves-Plaza, Mariely; Cruz, Iadelisse; Renta, Jessica Y.; Cadilla, Carmen L.; Feliu, Juan F.; Seip, Richard L.; Ruaño, Gualberto; Duconge, Jorge (Puerto Rico Health Sciences Journal, 2014)
Objective: This study was intended to determine the incidence rate of warfarinrelated adverse events (e.g., bleeding) in Puerto Ricans and whether a genetic association between warfarin pharmacogenes and any of these adverse events was observed over the initiation period (i.e., the first 90 days of therapy). Methods: We conducted an observational, retrospective cohort study of pharmacogenetic association in 122 warfarin-treated, male, Puerto Rican patients (69.9 ±9.6 years) from the Veterans Affair Caribbean Healthcare System (VACHS) who consented to participate. Genotyping was performed using the CYP2C9 and VKORC 1 assays by Luminex. Event-free survival curves were estimated using the Kaplan‒Meier method and analyzed by log-rank test. Cox regression models were constructed and hazard ratios (HR) calculated. Results: Carriers of functional CYP2C9 and VKORC1 polymorphisms demonstrated a higher incidence rate of multiple adverse events (i.e., 5.2 vs. 1.0 cases per 100 patient-months; RR = 4.8, p = 0.12) than did wild types. A significant association was observed between multiple adverse events and carrier status (HR = 2.5; 95% CI : 1.0‒6.3, p = 0.04). However, no significant associations between genotypes and individual outcomes over the first 90 days of therapy were found. Conclusion: The association of CYP2C9 and VKORC1 genotypes and risks for adverse events due to exposure to warfarin was examined for the first time in Puerto Ricans. Despite a lack of association with individual events in this study population, our findings revealed a potential utility of genotyping for the prevention of multiple adverse events during warfarin therapy.